The dynamics of street sexual harassment from the discourse of young men - Molina Rodríguez, Nancy Elizabeth; López Molina, Sergio Alberto; Chávez Torres, Guillermina (Facultad de Ciencias Políticas y Sociales, 2019)
In this work, we present an analysis of the discourse of a group of young men that attended a gender perspective workshop, and that have been generators and/or witnesses of the street sexual harassment. Feminist sociology was used as a theoretical perspective that allows us to observe the differences between men and women in public spaces. The research perspective is qualitative, which consists of making very detailed descriptions about people, situations, events, interactions and behaviors. The principal findings are the key moments of the dynamics of street sexual harassment, to undertake prevention actions.